High-Sensitivity Cardiac Troponin I Level and Left Ventricular Diastolic Dysfunction on Severe Preeclampsia: Kadar High Sensitivity Cardiac Troponin I dan Disfungsi Diastolik Ventrikel Kiri pada Preeklamsia Berat - Rahmad R. B. Wicaksono; Julian Dewantiningrum; Herman Kristanto (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: To know the relationship between high-sensitivity cardiac Troponin I (hscTnI) level with left ventricular dysfunction on severe preeclampsia.Methods: An observational analytics study with a cross-sectional approach of ten pregnant women with severe preeclampsia who underwent delivery or termination pregnancy and then performed a transthoracic echocardiography examination and serum levels of hscTnI.Results: There is a significant relationship between hscTnI levels and left ventricular diastolic dysfunction (p <0.05)Conclusion: These findings of this study have significant implications that severe preeclampsia is associated with heart remodelling and significant change in cardiac function especially left ventricular dilatation and elevation of hscTnI. Early identification and intervention may ameliorate subsequent cardiovascular disease so this requires regular and close follow-up of this target group.Keywords: high-sensitivity cardiac Troponin I, left ventricular diastolic dysfunction, severe preeclampsia. Abstrak Tujuan: Untuk mengetahui hubungan antara kadar high-sensitivity cardiac Troponin I (hscTnI) dengan disfungsi ventrikel kiri pada preeklamsia berat.Metode: Studi observasional dengan pendekatan potong lintang terhadap sepuluh ibu hamil dengan preeklamsia berat yang menjalani persalinan atau terminasi kehamilan kemudian dilakukan pemeriksaan ekokardiografi dan kadar hscTnI serum.Hasil: Ada hubungan yang bermakna antara kadar hscTnI dengan disfungsi diastolik ventrikel kiri (p <0,05).Kesimpulan: Temuan penelitian awal ini memiliki implikasi yang signifikan bahwa preeklamsia berat berhubungan dengan remodeling jantung dan perubahan signifikan pada fungsi jantung terutama dilatasi ventrikel kiri disertai peningkatan kadar hscTnI. Identifikasi dan intervensi dini dapat memperbaiki perjalanan penyakit kardiovaskular sehingga diperlukan pengawasan lanjut pada kelompok pasien ini.Kata kunci: disfungsi diastolik ventrikel, high-sensitivity cardiac troponin I jantung sensitivitas tinggi, kiri, preeklamsia berat